Implementasi Media Pembelajaran Power Point dalam Meningkatkan Minat Belajar pada Mata Pelajaran Fiqih Siswa Kelas VII di MTs Ainus Syamsi Kabupaten Maros - Muhammad Rifqi Abdullah; Agussalim Agussalim; Ana Cahayani Fatimah; Rosika Indri Karadona (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
This study aims to examine the implementation of PowerPoint learning media in increasing students' interest in learning Fiqh subjects for class VII at MTs Ainus Syamsi, Maros Regency. The background of this study is based on the low interest in learning of students which is indicated by their less active behavior, drowsiness, and lack of focus during learning. This study uses a descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study consisted of Fiqh subject teachers and class VII-C students totaling 28 people. The results of the study show that the use of PowerPoint media can significantly increase students' interest and involvement in the learning process. Attractive visual displays, such as images, colors, animations, and the insertion of quizzes or educational games, can create a more interactive and enjoyable learning atmosphere. In addition to increasing students' enthusiasm for learning, PowerPoint also makes it easier for teachers to deliver practical materials, such as ablution procedures, through systematic visualization. However, the effectiveness of this media is highly dependent on the presentation design and the teacher's ability to manage the class. Technical constraints such as limited tools and variations in students' visual interests are also challenges. Overall, PowerPoint has proven to be an effective and relevant media in increasing interest in learning, especially in learning Fiqh in today's digital era.